ANALISIS MOTIVASI BELAJAR SEJARAH DAN PENTINGNYA RASA CINTA TANAH AIR DALAM DIRI SISWA SMA PERTIWI 1 PADANG - Elsy Ramatika Ayu; Zafri Zafri (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
Motivation to learn history can be interpreted as a driving force for carrying out historical learning activities that come from within and also from outside the individual so as to foster enthusiasm in learning history. How strong an individual's motivation will determine the quality of the behavior he displays, one of which is the behavior of loving the motherland. A sense of love for the motherland needs to be cultivated in the soul of every individual from an early age who becomes a citizen of a country or nation so that the goal of living together can be achieved. This study aims to find out what is meant by motivation to learn history and how important is the feeling of love for the motherland in students. The essence of human beings as national and state creatures is to love their own nation and country. As a good citizen, you should have a sense of love for your nation. Proud to be part of the Indonesian nation is a light example in efforts to defend the country. The younger generation is one of Indonesia's assets in the future. Indonesian youth must have a strong sense of love for their country in order to become leaders in the future. Efforts to instill a cultural characteristic of this nation to differentiate it from people from other countries.In addition, the existence of a local culture that is inherent in Indonesian youth will be able to strengthen identity and pride as an Indonesian nation.